Antioxidant, Hepatoprotective Potential and Chemical Profiling of Propolis Ethanolic Extract from Kashmir Himalaya Region Using UHPLC-DAD-QToF-MS. (11th October 2015) - Wali, Adil F.; Avula, Bharathi; Ali, Zulfiqar; Khan, Ikhlas A.; Mushtaq, Ahlam; Rehman, Muneeb U.; Akbar, Seema; Masoodi, Mubashir Hussain
Abstract : The aim of this study was to examine hepatoprotective effect of ethanolic extract of propolis ( KPEt ) from Kashmir Himalaya against isoniazid and rifampicin (INH-RIF) induced liver damage in rats. Hepatic cellular injury was initiated by administration of INH-RIF combination (100 mg/kg) intraperitoneal (i.p.) injection for 14 days. We report the protective effects of KPEt against INH-RIF induced liver oxidative stress, inflammation, and enzymatic and nonenzymatic antioxidants. Oral administration of KPEt at both doses (200 and 400 mg/kg body weight) distinctly restricted all modulating oxidative liver injury markers and resulted in the attenuation of INH-RIF arbitrated damage. The free radical scavenging activity of KPEt was evaluated by DPPH, nitric oxide, and superoxide radical scavenging assay. The components present in KPEt identified by ultra high performance liquid chromatography diode array detector time of flight-mass spectroscopy (UHPLC-DAD-QToF-MS) were found to be flavonoids and phenolic acids. The protective efficacy of KPEt is possibly because of free radical scavenging and antioxidant property resulting from the presence of flavonoids and phenolic acids.